2020
DOI: 10.1016/j.breast.2020.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Orthotopic grafting of decellularized human nipple: Setting the stage and putative mechanism of healing

Abstract: A complex skin structure (such as a nipple) can be successfully decellularized under conditions that prevent extracellular matrix crosslinking or undue matrix degradation [1]. This treatment removes cellular antigens, thus mitigating immunorejection concerns and enabling allogeneic transplantation for nipple reconstruction after mastectomy. Non-human primate studies have shown that host-mediated revascularization and re-epithelization of the decellularized nipples occurs within six weeks and nipple projection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
(10 reference statements)
0
4
0
1
Order By: Relevance
“…22 This process prevents possible immune rejection of the graft, and also retains components that promote the activity of growth factors from both the patient and the graft to initiate re-epithelialization and re-vascularization and provide support for ingrowing cells. 23 Additionally, it is likely that the use of decellularized tissue will be uniquely beneficial for patients who have previously undergone radiation therapy. In cases of NAC replacement using a living autograft, radiation-related side effects, including delayed wound healing, adversely affect the re-vascularization process required to maintain living tissue, thereby resulting in NAC necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…22 This process prevents possible immune rejection of the graft, and also retains components that promote the activity of growth factors from both the patient and the graft to initiate re-epithelialization and re-vascularization and provide support for ingrowing cells. 23 Additionally, it is likely that the use of decellularized tissue will be uniquely beneficial for patients who have previously undergone radiation therapy. In cases of NAC replacement using a living autograft, radiation-related side effects, including delayed wound healing, adversely affect the re-vascularization process required to maintain living tissue, thereby resulting in NAC necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated that acellular nipple scaffolds (ANS) are free from cellular antigens and effectively cleared of DNA ( 145 ), using the same threshold of 50 ng/mg of tissue, thereby minimizing the risk of rejection by the recipient’s immune system. Moreover, these scaffolds maintain the integrity and bioactivity of the extracellular matrix, enabling successful reseeding with cells ( 146 , 147 ). They have also shown the capacity to support host-mediated re-cellularization with the growth of epithelial cells, neo-vasculature, and even nerve ingrowth ( 148 ).…”
Section: Literature Review Of Tissue- and Bio-engineering Approaches ...mentioning
confidence: 99%
“…Salah satu faktor yang mempengaruhi adalah faktor distensi uterus (Maternity, D, 2016). Faktor hormonal juga dapat mempengaruhi persalinan (Johnson PC, 2020). Hormon oksitosin dapat dihasilkan secara alamiah dari payudara yang dirangsang atau stimulasi puting susu pada ibu (Kuswanti, I, 2014).…”
Section: Pendahuluanunclassified